Lactation Performance, Milk Fatty Acid Composition, and Blood Lipid Profile of Lactating Buffaloes in Response to Dietary Soybean and Linseed Oils - E. Eldahshan; E. Saddick; S. Selim (Tropical Animal Science Journal, 2020)
There is an awareness in augmenting conjugated linoleic acid (CLA) and n-3 fatty acids (FA), while lowering saturated FA (SFA) in ruminant milk due to their advantageous health benefits for humans. Therefore, we aimed to investigate the effects of soybean and linseed oils on milk yield, milk composition, milk FA profile, and blood lipid metabolites. Eighteen multiparous Egyptian buffaloes fed corn silage and clover hay-based diet were allocated at random for body weight, days in milk, and milk yield into 3 groups of 6 buffaloes each using a randomized block design. Dietary treatments consisted of three concentrate supplements containing no additional plant oil (CON) or containing soybean oil (SO) or linseed oil at a level of 2.6% of dry matter intake (DMI) (400 g/head/d; 25.6 g/kg DMI). Moderate dietary inclusion of SO or LO had no detrimental effects on DMI, milk production, or milk fat per cent. Milk protein, lactose, ash, and total solids concentrations were increased by LO supplementation. The LO diet decreased milk total SFA content (C10:0, C12:0, C14:0, C16:0), augment monounsaturated FA (MUFA), 18:3n-3 FA, CLA, and polyunsaturated FA, as well as lower atherogenicity index and n-6:n-3 compared to CON. On the other hand, the SO diet increased milk fat content of n-6 FA, CLA, MUFA, and n-6:n-3, and decreased the atherogenicity index compared to CON. LO supplementation had no effect on serum concentrations of triglyceride, total lipids, HDL, and LDL. However, the SO group tended to have greater serum total lipids and LDL concentrations and significantly elevated level of serum cholesterol. In conclusion, dietary inclusion of LO in the concentrate supplement of dairy buffaloes could enrich the nutritive value of milk with advantageous FA (n-3 FA, MUFA, and CLA) and lower the atherogenicity index and n6 to n3 ratio without triggering any adverse effects on buffalo performance.